Liberação de arsênio de diferentes amostras contendo arsenopirita através da oxidação por oxigênio em meio circumneutro a alcalino - Nathália Augusta Ferreira Sales Coutinho (2019)
Arsenic release in aqueous solution from samples with different arsenopyrite contents (34.4 to 98.5% FeAsS) was investigated. The combined use of techniques such as MLA - Mineral Liberation Analyzer, X-ray diffraction, Raman spectroscopy and chemical analysis allowed the determination of the mineralogical composition of the samples. In three samples (AM-01 to AM-03) arsenopyrite was identified as single-phase containing arsenic (82.9 to 98.5% As). The sample AM-04 contained 50.7% of arsenopyrite and 9.9% of scorodite (FeAsO4.2H2O), besides the presence of 19.7% of pyrite (FeS2). The AM-05 sample contained 34.4% arsenopyrite, 35.9% lollingite (FeAs2), 9.9% pyrite, 4% quartz (SiO2) and 7.2% chalcopyrite (CuFeS2). The atomic composition of the arsenopyrite in the different samples, determined by electron microprobe, showed a variation in the As/Fe ratios of 1.06, 0.92, 0.89, 1.02, 1.06 and As/S ratio of 1.07, 0.87, 0.81, 0.92, 1.06, in samples AM-01 to AM-05 respectively. The AM-03 sample had the lowest As/Fe and As/S ratios. This variability can explain the observed differences in the intensities, in the full width at half maximum, and shifts in the position of the Raman bands in the samples. The As release experiments were carried out in jacked, nonstirred continuous, flow column at 25°C for 24 hours at pH = 5, 7 and 11 and in saturated O2 or N2 solutions. The results demonstrated the influence of mineralogy on the release of arsenic. The samples AM-04 and AM-05, which presented, respectively, the pyrite and scorodite or lollingite, scorodite and pyrite phases, released a higher amount of arsenic. For the richest samples, a tenfold difference in the amount of arsenic released by AM-01 and AM-02 samples was observed, compared to that released by AM03. The arsenic released and rate are reduced in the absence of O2 (100% N2), except for the richest sample of arsenopyrite (AM-03) at pH 7, for which both release and rates were not affected. In the presence of O2, the pH increase (5 to 11) reduced the arsenic release rates - from 10-8.8 to 10-9.3mol.m-2.s-1 (AM-01) and 10-8.8 and 10-9.1mol.m-2.s-1 (AM-02). Through Raman spectroscopy, the characteristic bands of iron oxyhydroxides, arsenates/arsenites, sulfur compounds (polysulfides) and sulfates were identified. The results suggest that differences in mineralogy, although not yet completely identified, may imply significant differences in arsenic released into the environment.